2020
DOI: 10.1101/2020.12.08.416701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure-based mapping of the TβRI and TβRII receptor binding sites of the parasitic TGF-β mimic, Hp-TGM

Abstract: TGF-β is a secreted signaling protein involved in many physiological processes: organ development, production and maintenance of the extracellular matrix, as well as regulation of the adaptive immune system. As a cytokine, TGF-β stimulates the differentiation of CD4+ T-cells into regulatory T-cells (Tregs) that act to promote peripheral immune tolerance. The murine parasite Heligmosomoides polygyrus takes advantage of this pathway to induce inducing Foxp3+ Tregs in a similar manner using a TGF-β mimic (TGM), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“… 16 A recent study of Hp‐ TGM binding to human receptors identified that domain 3 competes for the same binding sites as TGF‐β on TBRII, while domains 1 and 2 are required for optimal binding to TBRI, with the role of domains 4 and 5 in full‐length Hp‐ TGM remaining unclear. 31 It is important for future studies to understand which domains are required for Hp ‐TGM signaling in human cells, to solve the crystal structure of Hp ‐TGM and TβRI/II, and determine if Hp ‐TGM is able to bind other receptors. These data will provide clues as to how TGF‐β signaling pathways could be targeted therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“… 16 A recent study of Hp‐ TGM binding to human receptors identified that domain 3 competes for the same binding sites as TGF‐β on TBRII, while domains 1 and 2 are required for optimal binding to TBRI, with the role of domains 4 and 5 in full‐length Hp‐ TGM remaining unclear. 31 It is important for future studies to understand which domains are required for Hp ‐TGM signaling in human cells, to solve the crystal structure of Hp ‐TGM and TβRI/II, and determine if Hp ‐TGM is able to bind other receptors. These data will provide clues as to how TGF‐β signaling pathways could be targeted therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of immunity is inhibited by galectin in some parasites [79] and our pilot trials show that this is also true for H. polygyrus (unpublished observations). Two molecules influence the production of regulatory T cells: TGM which is a TGFβ mimic [108], and a large immunosuppressive molecule (MW 226,476) recently discovered by us (EGF-M) that contains 24 Epidermal Growth Factor-like (EGF-like) domains, 2 SEA domains and one von Willebrand factor A domain. Our pilot trials suggest that this molecule or its cleavage products bind epidermal growth factor receptor (EGFR), disrupt normal signalling and modulate the immune response to nematode infection.…”
Section: Immunomodulationmentioning
confidence: 99%